Hydrological modeling of Fecal Indicator Bacteria in a tropical mountain catchment. (1st August 2017) - Kim, Minjeong; Boithias, Laurie; Cho, Kyung Hwa; Silvera, Norbert; Thammahacksa, Chanthamousone; Latsachack, Keooudone; Rochelle-Newall, Emma; Sengtaheuanghoung, Oloth; Pierret, Alain; Pachepsky, Yakov A.; Ribolzi, Olivier
Abstract: The occurrence of pathogen bacteria in surface waters is a threat to public health worldwide. In particular, inadequate sanitation resulting in high contamination of surface water with pathogens of fecal origin is a serious issue in developing countries such as Lao P.D.R. Despite the health implications of the consumption of contaminated surface water, the environmental fate and transport of pathogens of fecal origin and their indicators (Fecal Indicator Bacteria or FIB) are still poorly known in tropical areas. In this study, we used measurements of flow rates, suspended sediments and of the FIB Escherichia coli ( E. coli ) in a 60-ha catchment in Northern Laos to explore the ability of the Soil and Water Assessment Tool (SWAT) to simulate watershed-scale FIB fate and transport. We assessed the influences of 3 in-stream processes, namely bacteria deposition and resuspension, bacterial regrowth, and hyporheic exchange (i.e. transient storage) on predicted FIB numbers. We showed that the SWAT model in its original version does not correctly simulate small E. coli numbers during the dry season. We showed that model's performance could be improved when considering the release of E. coli together with sediment resuspension. We demonstrated that the hyporheic exchange of bacteria across the Sediment-Water Interface (SWI) should be considered when simulating FIB concentration not only during wet weather, but also during the dry season, or baseflow period. In contrast, the implementation of the regrowth process did not improve the model during the dry season without inducing an overestimation during the wet season. This work thus underlines the importance of taking into account in-stream processes, such as deposition and resuspension, regrowth and hyporheic exchange, when using SWAT to simulate FIB dynamics in surface waters. Graphical abstract: Highlights: We implemented deposition/resuspension, regrowth and hyporheic exchange in SWAT. Overall, deposition and resuspension processes improved the E. coli simulation. The addition of hyporheic exchange improved E. coli simulation during low flow. Modified SWAT model should improve the evaluation of waste management options.